EGFL7 regulates sprouting angiogenesis and endothelial integrity in a human blood vessel model. (March 2019) - Usuba, Ryo; Pauty, Joris; Soncin, Fabrice; Matsunaga, Yukiko T.
Abstract: Elucidating the mechanisms underlying sprouting angiogenesis and permeability should enable the development of more effective therapies for various diseases, including retinopathy, cancer, and other vascular disorders. We focused on epidermal growth factor-like domain 7 (EGFL7) which plays an important role in NOTCH signaling and in the organization of angiogenic sprouts. We developed an EGFL7 -knockdown in vitro microvessel model and investigated the effect of EGFL7 at a tissue level. We found EGFL7 knockdown suppressed VEGF-A-induced sprouting angiogenesis accompanied by an overproduction of endothelial filopodia and reduced collagen IV deposition at the basal side of endothelial cells. We also observed impaired barrier function which reflected an inflammatory condition. Furthermore, our results showed that proper formation of adherens junctions and phosphorylation of VE-cadherin was disturbed. In conclusion, by using a 3D microvessel model we identified novel roles for EGFL7 in endothelial function during sprouting angiogenesis. Highlights: We report new roles of EGFL7 in VEGF-A-stimulated endothelial cells using a human blood vessel-on-a-chip model. This study reveals EGFL7 interferes with tip/stalk regulation, endothelium integrity, and phosphorylation of VE-cadherin. The microvessel model demonstrated its capacity to enable elaborate observations for a better understanding of vascular biology.